Philosophical standardism : an empiricist approach to philosophical methodology - Rescher, Nicholas (University of Pittsburgh Press, 1994)
Now in paperback, Philosophical Standardism is ideal for bringing one of the fields preeminent scholars into the classroom. In this novel empirical treatment of fundamental issues in philosophy, Nicholas Rescher propounds an unorthodox approach to philosophical doctrines that is predicated on the idea of standardism.